Editorial: Peritoneal Metastasis of Gastric Cancer: From Basic Research to Clinical Application - Zhou, Heng; Gao, Ziming; Sun, Anqi; Huang, Haibo; Zhang, Xiaotian; Li, Kai (Frontiers in Oncology, 2022)
Gastric cancer (GC) with a 5-year survival rate of 20%-40% is ranking the fifth for tumor incidence and the fourth for cancer-related mortality globally, which is responsible for over one million new diagnosed cases in 2020 and an estimated 769,000 deaths. Practically, poor prognosis and high mortality rate of GC are primarily due to metastasis. Notably, previous studies reported that almost 40% of patients with stage II-III gastric cancer were diagnosed with peritoneal metastases (PM) intraoperatively, and over 50% GC patients appear PM after radical resection. Particularly, GC patients with PM achieve exceptionally poor survival outcomes with a median overall survival of only 2-9 months. Biologically, PM is an extremely complicated process involving detachment from the primary tumor, seeding and survival in the cavum abdominis, adhesion to the peritoneum, invasion through the basement membrane to sub-peritoneal tissue, and proliferation with blood vascular neogenesis. Meanwhile, epithelial-mesenchymal transition (EMT) is essential for epithelial-derived malignant tumor cells to acquire the ability of migration and invasion, and cellular stemness can effectively suppress anoikis of free GC cells in the abdominal cavity and promote colonization in the peritoneal milky spots. Clinically, PM cannot be detected by conventional imaging techniques, intraperitoneal cytology or diagnostic laparoscopy due to unformed peritoneal cancer nodules or minimal exfoliated cancer cells. Therefore, the mechanism, diagnosis and treatment of PM remain daunting challenges in oncology. To effectively avert PM-related deaths, it is necessary to pay more attention to the fundamental and clinical research of PM.